2013
DOI: 10.1016/j.clay.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Pottery kiln and drying oven from Aventicum (2nd century AD, Ct. Vaud, Switzerland): Raw materials and temperature distribution

Abstract: Fireboxes of two pottery structures, excavated in 2002 at Aventicum (at present Avenches), the capital of Roman Switzerland, were studied to understand their function in the artisan quarter. Twenty-one oriented samples underwent petrographical, mineralogical and chemical analyses to determine the nature of the raw materials and the temperature distribution. Both structures are typologically different and show differing degrees of thermal impacts. Inferred maximum temperatures for kiln Structure 6, as deduced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In this paper, we report the results obtained from ceramic tests prepared with a clay of the first type, which could be assimilated to earthenwares produced by primary clays (e.g. Smith, 2000;Buxeda I Garrigòs et al, 2003;Eramo and Maggetti, 2013).…”
Section: -850åcmentioning
confidence: 99%
“…In this paper, we report the results obtained from ceramic tests prepared with a clay of the first type, which could be assimilated to earthenwares produced by primary clays (e.g. Smith, 2000;Buxeda I Garrigòs et al, 2003;Eramo and Maggetti, 2013).…”
Section: -850åcmentioning
confidence: 99%
“…The well sorted inclusions suggest sieving procedure and a good selection of the raw material for the Israeli samples. The homogeneous reddish calcareous matrix suggests a very similar production technology for the two archaeological sites with controlled oxidized firing conditions .…”
Section: Resultsmentioning
confidence: 99%
“…In our case, however, there is no archaeological or geological evidence to support a similar assumption. A literature survey revealed that Ca‐poor or noncalcareous clays seem to have been used for the production of Roman brittle ceramics from the Near East and Turkey (Bartl, Schneider, & Bohme, ; İssi, Özçatal, Kara, & Alp, ), amphorae from Italy (Ceccarelli et al, ) or even for bricks and clay binders for pottery kiln in Switzerland (Eramo & Maggetti, ). Such observations can be expected due to the lower thermal expansion coefficient of the noncalcareous clay as compared to the Ca‐rich meaning that the latter are more prone to change in their shape and volume with the increasing temperature (Tite, Kilikoglou, & Vekinis, ).…”
Section: Discussionmentioning
confidence: 99%